An Analysis of Meaning Equivalence in the Translation of English Idioms into Indonesian in the Novel Harry Potter and the Sorcerer’s Stone - Indah Retno Sari; Nurfithri Nurfithri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines meaning equivalence in the translation of English idiomatic expressions into Indonesian in Harry Potter and the Sorcerer’s Stone. The research focuses on identifying idiomatic expressions, analyzing the translation strategies employed, and evaluating the extent to which meaning equivalence is achieved in the Indonesian version, Harry Potter dan Batu Bertuah. A qualitative descriptive approach was adopted using comparative textual analysis and content analysis. Data were collected through close reading of the source and target texts, followed by the identification and classification of idiomatic expressions and their translations. The findings reveal that translation by paraphrase is the most frequently employed strategy, particularly when direct idiomatic equivalents are unavailable in the target language. Cultural substitution and the use of expressions with similar meaning but dissimilar form are also utilized to maintain communicative effectiveness and cultural acceptability. The results indicate that the translator consistently prioritizes dynamic and pragmatic equivalence, enabling the translated text to preserve meaning, readability, and narrative impact while remaining natural for Indonesian readers.